Analisis Perkembangan Infrastruktur Land Side di Bandara Udara H. Hasan Aroeboesman Ende Dari Tahun 2015-2022 - Ruing, Abdul Majid Rizkian; Jumlad, Walid (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Infrastructure development is a process of increasing facilities to support the needs of each user in an environment or institution. In this case the airport infrastructure, especially in the Land Side area, of course always makes progress both in terms of service and functionality to guarantee fulfillment the needs of passengers using air transportation services at each airport. The Land Side area is an area without borders, which is very important to support all the needs of passengers and visitors. This study uses a descriptive qualitative approach, namely the data used are primary and secondary data. Primary data itself is the data obtained through direct observation, interviews and documentation, while secondary data is data obtained based on pre-existing information that was deliberately collected by the author to complement research needs. The results of this study can be concluded that the Development of Land Side Infrastructure at H. Hasan Aroeboesman Ende Airport from 2015 - 2022 has carried out changes and improvements to infrastructure as a facility to support passenger needs properly. The development of this airport has obstacles, namely in terms of land acquisition, because the location of the area is directly adjacent to settlement residents and schools, so the solution is for the airport and the Regional Government of Ende Regency to take a direct approach with local residents and the school to be willing allocated. So the conclusion is that the Development of the Transportation Sector in Ende Regency aims to obtain improvements, both main and supporting facilities, infrastructure and facilities, by creating safe, comfortable and orderly transportation facilities. Keywords: Development, Infrastructure,Land Side, Obstacle